KREATIVITAS SENI UNTUK LANSIA: SOLUSI MENGHADAPI STRES DAN MENINGKATKAN KEBAHAGIAAN PADA LANSIA DI PANTI WERDHA X - Valensia Teresa; Syaqila Novarianty; Vian Stanly Immanuel Rumainum; Hanna Christina Uranus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Aging is a natural phase marked by physical, psychological, and social changes that can affect the quality of life of the elderly. In Indonesia, the elderly population continues to grow, including those residing in nursing homes (panti werdha). They often face issues such as stress, loneliness, and a lack of meaningful activities. Observations at the Islamic Village Nursing Home revealed that many elderly residents experience boredom due to monotonous routines and limited social interaction. To address this issue, a team of university students conducted a humanitarian project through the Merdeka Belajar Kampus Merdeka (MBKM) program aimed at improving the quality of life of the elderly through art and craft activities. The activities included drawing, coloring, making bracelets, and crafting flowers from felt fabric. This program employed a qualitative descriptive approach using observations and interviews with both the elderly participants and the nursing home staff to assess the impact on stress levels and emotional well-being. The program was implemented from February 17 to June 13, 2025, with a frequency of three sessions per week. Each activity was designed to encourage self-expression, enhance creativity, and strengthen social interaction among the elderly. The results showed a decrease in stress, improved mood, and a greater sense of happiness and appreciation. Several participants reported feeling more productive and joyful after joining the activities. This project demonstrates that structured creative interventions can significantly enhance the emotional well-being and overall quality of life of elderly residents in nursing homes.